2010
DOI: 10.1002/cbic.200900635
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Lipase‐Catalyzed Kinetic Resolution of Bulky Phenyl Alkyl sec‐Alcohols: A Thermodynamic Analysis of Enantioselectivity

Abstract: The size of the stereoselectivity pocket of Candida antarctica lipase B limits the range of alcohols that can be resolved with this enzyme. These steric constrains have been changed by increasing the size of the pocket by the mutation W104A. The mutated enzyme has good activity and enantioselectivity toward bulky secondary alcohols, such as 1-phenylalkanols, with alkyl chains up to eight carbon atoms. The S enantiomer was preferred in contrast to the wild-type enzyme, which has R selectivity. The magnitude of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…To obtain ( S )‐selective mutants for rac ‐ 1 a , which meant inverting the Kazlauskas rule, the stereoselective pocket of alcohols should be changed to accommodate the phenylalkanol substituents, which are larger than the ethyl group. An early study has identified W104 as the most important hot spot in the alcohol‐binding pocket of CALB for the reversed ( S )‐selectivity of sec ‐alcohols, and W104 should be replaced by smaller amino acids to enlarge the volume of the stereoselectivity pocket. According to the X‐ray structure of CALB (PDB code 1TCA, Figure A), we selected four important hydrophobic residues W104, L278, A281 and A282 (sites A, C, and B as shown in Figure B) surrounding the alcohol‐binding pocket as mutagenesis targets.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To obtain ( S )‐selective mutants for rac ‐ 1 a , which meant inverting the Kazlauskas rule, the stereoselective pocket of alcohols should be changed to accommodate the phenylalkanol substituents, which are larger than the ethyl group. An early study has identified W104 as the most important hot spot in the alcohol‐binding pocket of CALB for the reversed ( S )‐selectivity of sec ‐alcohols, and W104 should be replaced by smaller amino acids to enlarge the volume of the stereoselectivity pocket. According to the X‐ray structure of CALB (PDB code 1TCA, Figure A), we selected four important hydrophobic residues W104, L278, A281 and A282 (sites A, C, and B as shown in Figure B) surrounding the alcohol‐binding pocket as mutagenesis targets.…”
Section: Resultsmentioning
confidence: 99%
“…Next, the substrate range of the best ( S )‐selective mutant WB15 evolved for the model substrate rac ‐ 1 a was determined. Moreover, considering that all previous studies on ( S )‐selectivity of W104A (WB2) were carried out for the acylation reaction of racemic phenylalkanols in nonaqueous media, it is valuable to determine the stereoselectivity of W104A in the hydrolytic kinetic resolution of phenylalkanol esters. The comparison results of WT, WB2 and the best WB15 variants as the catalysts for hydrolytic kinetic resolution of a series of phenylalkanol esters are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some examples revealed that there was an interesting relationship between the size of substrates and the reshaped active pockets of enzymes . Hult and coworkers reported that the mutant W104A of Candida antarctica lipase B had increased enantioselectivity toward various secondary alcohols with increasing chain length of the alkyl moiety on the chiral central atom . It would be expected that in the restricted space of the reshaped pocket, an array of compounds with the increasing chain length would face the decreasing degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%
“…It is known, that the temperature can influence both the E and the reaction rate of a lipase-catalysed reaction. 136,137 Therefore, reactions were performed at 2, 25 and 30 °C. The E and the reaction rate increased slightly with increasing temperature.…”
Section: Enzymatic Experimentsmentioning
confidence: 99%